Efficacy and Safety of Rivaroxaban Compared with Other Therapies Used in Patients with Peripheral Artery Disease Undergoing Peripheral Revascularization: A Systematic Literature Review and Network Meta-Analysis - Rupert Bauersachs; Olivia Wu; Neil Hawkins; Kevin Bowrin; Piotr Wojciechowski; Emilie Clay; Maria Huelsebeck (Hindawi-Wiley, 2021)
Background. The guidelines on antithrombotic treatment in patients with symptomatic peripheral artery disease (PAD) undergoing peripheral revascularization of the lower extremities were developed based on heterogeneous trials, assessing various dose regimens and recruiting patients who were subjected to different revascularization procedures. Objective. To compare efficacy and safety of treatments used in patients with PAD undergoing peripheral revascularization accounting for between-trial heterogeneity and large dispersion of the quality of evidence. Methods. A systematic literature review of randomised controlled trials (RCTs) recruiting adult patients with PAD receiving antithrombotics was conducted until January 2020. Hazard ratios (HR) were pooled using Bayesian network meta-analysis. The estimated between-treatment effects were presented as HR together with 95% credible intervals. The base case analysis included studies recruiting patients following recent peripheral revascularization, who received treatment regimens administered within the recommended therapeutic window, while a sensitivity scenario included all identified trials. Results. Thirteen RCTs were identified (8 RCTs enrolled patients following peripheral revascularization and 5 RCTs regardless of the previous revascularization). Five trials, recruiting an overall of 8349 patients, were considered for the base case analysis. Of those, 6564 patients were recruited in the VOYAGER PAD trial comparing rivaroxaban plus aspirin (RIV plus ASA) versus ASA. RIV plus ASA was associated with a lower risk of repeated peripheral revascularization versus ASA monotherapy (HR=0.88 [0.79, 0.99]), however having a trend towards an increased rate of major bleeding (HR=1.43 [0.98, 2.11]). There was no evidence for differences between RIV plus ASA and dual antiplatelet therapy and vitamin K antagonists plus ASA. Similar results were observed in sensitivity analyses. Conclusions. RIV plus ASA is associated with reduced risk of revascularization compared with ASA monotherapy, but the evidence for other comparators, in particular antiplatelet regimens, was insufficient to guide treatment decisions and highlights the challenge in establishing the magnitude of comparative efficacy using existing RCTs.